2003
DOI: 10.1063/1.1621064
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin resonance probe based on a 100 μm planar microcoil

Abstract: We describe the fabrication and the performance of a microcoil-based probe for electron spin resonance (ESR) spectroscopy on micrometer sized samples. The probe consists of a 100 μm planar microcoil fabricated on a glass substrate, tuned and matched at 1.4 GHz (L band) using miniaturized ceramic capacitors. We performed continuous wave ESR experiments on samples having a volume between (100 μm)3 and (10 μm)3. At 300 K, we achieved a spin sensitivity of about 1010 spins/G Hz1/2, which is comparable to that of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…The cw EPR operation of a microcoil-based probe on micrometer-sized samples was recently demonstrated at 1.4 GHz (L band) [29]. At 300 K, a spin sensitivity of about 10 10 spins AE G À1 Hz À1/2 was achieved, which is already comparable to that of a commercial X-band spectrometer.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…The cw EPR operation of a microcoil-based probe on micrometer-sized samples was recently demonstrated at 1.4 GHz (L band) [29]. At 300 K, a spin sensitivity of about 10 10 spins AE G À1 Hz À1/2 was achieved, which is already comparable to that of a commercial X-band spectrometer.…”
Section: Introductionmentioning
confidence: 56%
“…For the microstrip resonator with an incorporated microcoil the signal calculated using Eq. (2) of [29] exceeds the experimentally observed signal by a factor of 3, and for the PMR with the radial stub by a factor 1.5. The calculation was done assuming that the DPPH samples are far from saturation, whereas in the experiment they are partially saturated.…”
Section: Cw Eprmentioning
confidence: 93%
See 2 more Smart Citations
“…Concerning the development of on-chip MW structures, there are already many studies performed on the on-chip spiral coil structure [16]. We followed these studies and developed the on-chip spiral coil shown in Fig.…”
Section: B Numerical Calculationsmentioning
confidence: 99%